Analisis Kegiatan Komunikasi Pemasaran Cafe Sekala Rooftop Dalam Meningkatkan Minat Pembeli Di Masa Pandemi Covid-19 - Rhesabahi, Sany; Putri, Yuliani Rachma (eProceedings of Management, 2023)
The pandemic period that has occurred in Indonesia has had a negative impact on all sectors, especially the industrial and trade sectors, ranging from large scale to small business scale. Various restrictions on activities were implemented, so trading business activities were pushed into a situation where sales and marketing activities underwent changes. Many business activities have also switched to online platforms. Café Sekala's management implements appropriate and relevant marketing communication activities in order to maintain the loyalty of its customers through Instagram social media, so that Café Sekala is able to survive during the pandemic when many other cafes decided to close temporarily or permanently. The purpose of this research is to find out how the marketing activities carried out by Café Sekala Rooftop have increased buyer interest and been able to maintain the Café during a pandemic. The theory used is the theory of marketing communications with the marketing communications mix put forward by Kotler and Armstrong. This study used qualitative research methods and data collection was carried out through interviews with informants and direct observation in the field. The results of the study show that Café Sekala Rooftop uses marketing communication theory with a marketing communications mix in marketing its products and place of business.Keywords-Marketing Communication, Marketing Communication Mix